More about legs-trunk factor - Kleshnev, V. (Rowing Biomechanics Newsletter, 2015)
On the role and training of legs-trunk-coordination in Rowing. Conclusion: ergometers with mobile footstretchers have much a better correlation with onwater rowing in terms of legs-trunk coordination and rowing style. Extensive training on stationary ergs could change rowing style towards higher usage of upper body after the catch, which may have a negative effect on rowing technique in a boat.